Exploring How Integrating Art & Animation in Teaching Text-Based Programming Affects High School Students' Interest in Computer Science - Mohammed Jawad, Hadeel (ProQuest Dissertations & Theses, 2018)
As oil is the fuel of the industrial society, software is the fuel of our current information society. According to the Bureau of Labor Statistics, there will be more demand for computing jobs in the future. By 2024, more than one million computing jobs will be available. Statistics show that there is more demand for computing jobs than there is a supply of qualified graduates from universities. In this experimental study, three groups of high school students were targeted to explore how integrating art, animation, and code sharing into programming affects their interest in pursuing a degree in computer science (CS) after graduation. Moreover, the study also explored the effect of social factors and attitudes of the students toward programming and a CS degree. Pretest-posttest survey questionnaires were used to measure the study variables before and after taking a programming course. A new web-based learning environment was developed and used as a treatment in this study. The developed tool included the use of art, animation, and code sharing to increase students' motivation in learning computer programming. Three groups of students from Ann Arbor public and private schools participated in this study with different coding time. The demographic data were also collected and analyzed in this study. The field of CS is currently dominated by White and Asian males. This study also aimed to encourage and increase the motivation of female and underrepresented racial groups towards CS. The results of this study showed that the use of art, animation, and code sharing increased students' knowledge, enjoyment, and motivation in learning computer programming. It thereby increased their interest in pursuing a degree in CS after graduation.